All judges are political--except when they are not : acceptable hypocrisies and the rule of law - Bybee, Keith J., 1965- (Cultural lives of law., 2010)
"The legitimacy of our courts rests on their capacity to give broadly acceptable answers to controversial questions. Yet Americans are divided in their beliefs about whether our courts operate on unbiased legal principle or political interest. Comparing law to the practice of common courtesy, Keith Bybee explains how our courts not only survive under these suspicions of hypocrisy, but actually depend on them."--[book cover]